2022
DOI: 10.1111/ddi.13580
|View full text |Cite
|
Sign up to set email alerts
|

Spatio‐temporal turnover and drivers of bentho‐demersal community and food web structure in a high‐latitude marine ecosystem

Abstract: Aim: Assess the spatial and temporal turnover of bentho-demersal marine fauna by integrating ecological metrics at the community and food web levels and evaluate their main environmental and anthropogenic drivers.Location: Barents Sea. Method:We analysed data of benthic and bentho-pelagic fish and megabenthic invertebrates caught in the Barents Sea ecosystem survey in August-September 2009-2017 to characterize the spatial and temporal variability of bentho-demersal communities and food webs. We used a trait da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 112 publications
(149 reference statements)
0
5
0
Order By: Relevance
“…This study found that the variation of phytoplankton communities during summer bloom successions was closely associated with the changes in abiotic environmental factors (i.e., T, TN, and PO 4 3− ) and viral factors (i.e., VA, VLP, FLP, and VLB; Table 2 ; Figures 6 , 7 ). Hierarchical partitioning method has been widely used to estimate the individual importance of each explanatory variable ( Li et al, 2022 ; Pecuchet et al, 2022 ). Based on the hierarchical partitioning analysis, the viral variables still have a marked effect on the dynamics of phytoplankton community, although the environmental attributes were the major factors ( Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…This study found that the variation of phytoplankton communities during summer bloom successions was closely associated with the changes in abiotic environmental factors (i.e., T, TN, and PO 4 3− ) and viral factors (i.e., VA, VLP, FLP, and VLB; Table 2 ; Figures 6 , 7 ). Hierarchical partitioning method has been widely used to estimate the individual importance of each explanatory variable ( Li et al, 2022 ; Pecuchet et al, 2022 ). Based on the hierarchical partitioning analysis, the viral variables still have a marked effect on the dynamics of phytoplankton community, although the environmental attributes were the major factors ( Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Understanding how geographic shifts affect marine communities at a finer geographic scale within the study areas considered here remains a present and future challenge. Even though very recent studies report no clear sub-regional temporal community trends across the Barents Sea, these could be hard to detect due to interannual variability in community composition at smaller scales ( Pecuchet et al, 2022 ). Moreover, our results contain surveys from only one season in each study region, which could be partially influenced by seasonal changes in species abundance and biomass, as observed in other marine ecosystems ( Lloret-Lloret et al, 2021 ; Vilas et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Weakening of the pelagic-benthic coupling through the decrease in vertical export efficiency and amount of sinking labile organic matter will have repercussions on arctic deep-sea ecosystems. Indeed, benthic biomass and diversity were found to be higher in the seasonally ice-covered areas (Pecuchet et al 2022) with a shorter but with higher modularity food web. Modelling results indicate that climate-related changes in phytodetrital inputs can lead to important shifts in benthic biomass, community structure, and functional diversity, with loss of various common taxa (Lovvorn et al 2016).…”
Section: Longer Productive Season and Food Base Composition Change/mi...mentioning
confidence: 94%